Clear Cell Carcinoma Arising from Ovarian and Thoracic Endometriosis: A Case Report and Review of Literature - Samantha Mendoza Stanteen; Taemee Pak; Hao Chen; Matthew Carlson; Jessica Lee (Case Reports in Obstetrics and Gynecology)
We report a case of stage IVB ovarian clear cell carcinoma in a 35-year-old female with a long-standing history of biopsy-proven pelvic and thoracic endometriosis. At the time of her ovarian cancer diagnosis, her tumors were found to be isolated to the sites of her previously known endometriotic lesions, suggesting that malignant transformation of her endometriosis to ovarian cancer had occurred. She underwent primary tumor debulking, then received six cycles of intravenous carboplatin and paclitaxel, and is now free of disease. We have conducted a literature review of ovarian cancers arising from endometriosis as well as a summary of the molecular basis on the relationship between endometriosis and malignant ovarian carcinoma.